Factors associated with intubation and heated high-flow nasal cannula use in hospitalized respiratory syncytial virus infected children: A single-center retrospective cohort study. - Nichaphat Keelapang; Kanokkarn Sunkonkit (PLoS ONE)
Background Respiratory syncytial virus (RSV) is a leading cause of severe lower respiratory tract illness (LRTI) in children, often requiring hospitalization and respiratory support. This study, therefore, aims to identify factors associated with intubation and heated high-flow nasal cannula (HHFNC) use in children hospitalized with RSV infection. Methods This retrospective study reviewed medical records of children aged 0 month to 15 years hospitalized with RSV infection at Chiang Mai University Hospital between January 2018 and December 2022. Baseline characteristics, clinical features, and laboratory findings were analyzed. Factors associated with intubation or HHFNC use were analyzed using univariable and multivariable logistic regression with significance set at p < 0.05. Result Among 260 children (53.8% male; median age 28 months, IQR 12-44), 76.5% required low-flow oxygen therapy, 11.5% required HHFNC, and 11.9% required intubation, respectively. Prematurity (22.7%) and respiratory comorbidities (17.6%) were common. HHFNC use was significantly associated with prematurity (adjusted odds ratio [aOR] 3.11, p = 0.016), chest retractions (aOR 5.42, p = 0.017), and multi-lobar infiltrates on chest X-ray (aOR 7.52, p < 0.001). Factors associated with intubation included age ≤ 2 years (aOR 3.70, p = 0.008), prematurity (aOR 5.68, p < 0.001), chest retractions (aOR 4.39, p = 0.033), and multi-lobar infiltrates (aOR 8.83, p < 0.001). Conclusions Prematurity, younger age, chest retractions, and multi-lobar infiltrates on chest X-ray were key predictors for HHFNC and intubation in RSV-infected children. These findings may inform risk stratification and management strategies for severe RSV-related illness in pediatric patients.